Reconstruction of Hegemonic Gender Beliefs through Fairy Tales: A Critical Discourse Analysis of Nepali Version of “Hansel and Gretel” - Laudari, Sarita (Campion Journal of Multidisciplinary Research and Explorer, 2025)
Fairy tales are such discourse that influence the ideology of children, who grow up by listening to them. In present technological world, there is high access to digital version of the fairy tales along with Nepali translation. These stories play important roles in constructing gender ideology in children. For this reason, what sort of stories should be accessed to children is a major concern, and how the fairy tales as a discourse communicate and influence in reconstruction of ideology and gender belief is the problem this research focuses on. In this regard, this research aims to explore how discourse of fairy tales reconstructs hegemonic cultural beliefs of gender. This research is based on qualitative method of critical discourse analysis aiming to explore submerged power structures and the role of discourse in reflecting and constructing social realities. Critical discourse analysis has been used to analyse its language, and to explore how language can reflect dominant gendered views and practices. The analysis shows that language used in the story “Hansel and Gretel” is gender biased presenting female and male characters with stereotypical gender roles. It shows biased representation of male and female characters, which contributes to reconstruct cultural gender beliefs. This paper explores the need of recreation of fairy tales with gender sensitive language as they have wider influence on power structures in social practice.